Delta Inulin Adjuvant Enhances Plasmablast Generation, Expression of Activation-Induced Cytidine Deaminase and B-Cell Affinity Maturation in Human Subjects Receiving Seasonal Influenza Vaccine - Li, Lei; Honda-Okubo, Yoshikazu; Li, Connie; Sajkov, Dimitar; Petrovsky, Nikolai (PloS one, 2015)
There is a major need for new adjuvants to improve the efficacy of seasonal and pandemic influenza vaccines. Advax is a novel polysaccharide adjuvant based on delta inulin that has been shown to enhance the immunogenicity of influenza vaccine in animal models and human clinical trials. To better understand the mechanism for this enhancement, we sought to assess its effect on the plasmablast response in human subjects. This pilot study utilised cryopreserved 7 day post-vaccination (7dpv) peripheral blood mononuclear cell samples obtained from a subset of 25 adult subjects from the FLU006-12 trial who had been immunized intramuscularly with a standard dose of 2012 trivalent inactivated influenza vaccine (TIV) alone (n=9 subjects) or combined with 5mg (n=8) or 10mg (n=8) of Advax adjuvant. Subjects receiving Advax adjuvant had increased 7dpv plasmablasts, which in turn exhibited a 2-3 fold higher rate of non-silent mutations in the B-cell receptor CDR3 region associated with higher expression of activation-induced cytidine deaminase (AID), the major enzyme controlling BCR affinity maturation. Together, these data suggest that Advax adjuvant enhances influenza immunity in immunized subjects via multiple mechanisms including increased plasmablast generation, AID expression and CDR3 mutagenesis resulting in enhanced BCR affinity maturation and increased production of high avidity antibody. How Advax adjuvant achieves these beneficial effects on plasmablasts remains the subject of ongoing investigation. Australia New Zealand Clinical Trials Register ACTRN12612000709842 https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=362709.